Modelling soil-water behavior in oil palm plantations using Neutron Moisture Meter (NMM) and Resistivity Imaging System (RIS) - Rajoo, K. S.; Yusop, Z.; Mejus, L.; Gerusu, G. J (Malaysian Society of Soil Science, 2022)
Water management is rarely a focus in Southeast Asian oil palm plantations, due to high rainfall all year long. However, this climatic condition is changing. There is increasing evidence that climate change is causing tropical regions to have reduced annual mean precipitation and increased prevalence of dry seasons. Thus, knowledge gaps in the area of soil-water relationship in these agricultural systems will result in inefficient water management. Therefore, this study was conducted to evaluate the potential of two approaches in monitoring and modelling soil water behaviour under oil palm canopies. The first approach used Neutron Moisture Meter (NMM), to obtain a time series on Θ, including evaluating soil-rainfall relationship. The second approach used Resistivity Imaging System (RIS), to provide data on stratigraphy that was used to further characterize the geologic setting of soil (6 m depth) and its effects on soil moisture. The results revealed a small significant variability in Θ values in the 20 different soil depths. Θ values also showed significant increases in response to high rainfall events (>30.0 mm) which decreased with time. Soil-water content percentage changes ranged from 9.5 to 23.8% at different depths. The resistivity imaging surveys successfully mapped the soil water content underneath the oil palm catchment up to 6 m depth, revealing leakages to groundwater flow at some study sites. Both techniques (NMM and RIS) were able to model the soil-water relationship in oil palm plantations. These methods can be used to charter better water management strategies in oil palm plantations in the future.